IMPLEMENTASI DAN EFEKTIFITAS PENGGUNAAN MOBILE LEARNING TERHADAP HASIL BELAJAR MAHASISWA PROGRAM STUDI SISTEM INFORMASI STIKOM UYELINDO KUPANG - Sumarlin, Sumarlin; Malahina, Edwin A. U. (HOAQ (High Education of Organization Archive Quality) : Jurnal Teknologi Informasi, 2020)
This research was made aiming to implement and improve the effectiveness of learning media through mobile-based mobile learning for all courses in Uyelindo Kupang STIKOM information system students. The research target to be achieved is an additional learning media that is interesting and easy to use so that it can increase student interest and student achievement. This research will discuss how to design, develop and evaluate the effectiveness of using Mobile Learning applications. This application is made so that students can easily access a course material using the Mobile Learning application by Smartphone and also to increase the effectiveness of conducting online lectures at the Uyelindo Kupang STIKOM information system study program. To measure the effectiveness of the use of mobile learning it is necessary to test among them, from the results of the Kolmogorov-Smirnov test using SPSS 16 it is found that the research subjects are normally distributed and based on the results of the Paired Samples Test t-test it is known that the significant value is 0,000> 0,05. While t-count = -11,142 and for t-table at a significant level ? = 5% (0.05) with degrees of freedom (df) n-1 or 50-1 = 49. Two-sided testing (significance = 0.025) results are obtained for t-table = 2 , 00958 with a significant level of 0.025. In the result t-count < t-table (-11.142 <2, 00958) then H0 is rejected and Ha is accepted. So that the use of mobile learning media can improve student learning outcomes at the Uyelindo Kupang STIKOM information system.